Preparation method of medical attapulgite particles with spherical porous structure

The preparation of spherical porous concave rod microspheres with spherical porous structures through ball milling, ultrasonic dispersion and electrostatic spraying methods has solved the problem of poor fluidity and dispersion of concave rod materials, and achieved more efficient drug carrier performance and biomedical application effects.

CN119899048APending Publication Date: 2025-04-29ANHUI SHUANGFENG NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510067912.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The concave and convex rod material has poor fluidity and dispersion due to irregular powder morphology, and the messy pore structure affects its application effect as a drug carrier.

Method used

The concave and convex rod powder was treated by ball milling, and then mixed with surfactant, anhydrous ethanol and pore-forming agent by ultrasonic dispersion, and microspheres with spherical porous structures were prepared by electrostatic spraying. Finally, the concave and convex rod particles with spherical porous structures were obtained by high temperature sintering.

Benefits of technology

The fluidity and dispersion of the concave and convex rod material is improved, its adsorption ability as a drug carrier is enhanced, and the internal porosity of the microspheres is adjusted, which improves the application effect in the field of biomedicine.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899048A_ABST
    Figure CN119899048A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of medical attapulgite particles with a spherical porous structure, which comprises the following steps: firstly, wet-grinding attapulgite powder in any solution of diluted hydrochloric acid, dilute sulfuric acid or oxalic acid, washing with deionized water after sufficient ball-milling, sufficiently drying, and sieving to obtain micron-sized uniform powder particles; secondly, precursor electronic injection liquid formed by mixing absolute ethyl alcohol, a surface active agent, a pore forming agent and attapulgite powder according to a certain proportion is prepared; finally, after full stirring, the electronic injection liquid is filled into an injector, microspheres are prepared through an electrostatic spraying device, and the attapulgite microspheres with high sphericity, high specific surface area and high porosity can be obtained after drying and high-temperature sintering. The adsorption effect of the attapulgite is fully exerted, and the hemostasis efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of porous ceramic microsphere material preparation, in particular to a method for preparing medical attapulgite particles with a spherical porous structure. Background Art

[0002] As a natural magnesium-aluminum silicate clay mineral, attapulgite has a one-dimensional short rod or fiber structure. Usually, the diameter of a single fiber is about tens of nanometers and the length can reach several microns. Single rod crystals can form irregular attapulgite particles through aggregation and accumulation. The internal pore structure is very rich, so it has a high specific surface area and excellent adsorption performance. At the same time, attapulgite has good biocompatibility and has great application potential in the high value-added biomedical field.

[0003] Although attapulgite is abundant in reserves and cheap, and has a wide range of application potential in the field of biomedicine, attapulgite generally exists in the form of irregular powder, resulting in poor fluidity and dispersibility in solution, and the messy pore structure may also cause certain adverse effects when it is used as a drug carrier. Therefore, how to give full play to the properties of attapulgite and improve the application effect of attapulgite materials is an urgent problem to be solved. Summary of the invention

[0004] The purpose of this section is to summarize some aspects of the embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0005] Therefore, the purpose of the present invention is to provide a method for preparing medical attapulgite particles with a spherical porous structure, which effectively solves the problems of poor fluidity and low dispersibility of the above-mentioned attapulgite and improves its application effect in the field of biomedicine.

[0006] To solve the above technical problems, according to one aspect of the present invention, the present invention provides the following technical solutions:

[0007] A method for preparing medical attapulgite particles with a spherical porous structure, comprising the following steps:

[0008] S1, weighing attapulgite powder and putting it into a ball mill, adding zirconium oxide grinding balls, anhydrous ethanol and acid solution in proportion, and fully ball milling, washing with deionized water, drying and sieving to obtain attapulgite powder of uniform size;

[0009] S2, mixing the obtained attapulgite powder with a surfactant, anhydrous ethanol, and a pore-forming agent in proportion, and uniformly dispersing the mixture by ultrasonication in a 50-70° C. water bath or oil bath to obtain an electrospray precursor solution;

[0010] S3, loading the obtained electrospray precursor solution into a push injection device, the microsphere receiving device is filled with a mixed solution of dilute hydrochloric acid and anhydrous ethanol, applying voltage to the push injection device for electrospraying, and obtaining microspheres in the microsphere receiving device;

[0011] S4. The obtained microspheres are washed with deionized water, dried at 100° C. for 2-3 hours, and then sintered at high temperature to obtain attapulgite microspheres with a spherical porous structure.

[0012] As a preferred embodiment of the method for preparing the medical attapulgite particles with a spherical porous structure described in the present invention, in step S1, the mass ratio of attapulgite powder, anhydrous ethanol, acid solution and zirconium oxide grinding balls is 1:2:2:5.

[0013] As a preferred scheme of the preparation method of the medical attapulgite particles with a spherical porous structure described in the present invention, wherein, in step S1, the zirconium oxide grinding balls include large balls with a diameter of 1 mm and small balls with a diameter of 0.2 mm, the mass ratio of the large balls to the small balls is 1:4, the ball milling time is 6-8 hours, and the rotation speed is 1000-2000r / min.

[0014] As a preferred embodiment of the method for preparing the medical attapulgite particles with a spherical porous structure described in the present invention, in step S1, the acid solution is any one of dilute hydrochloric acid, dilute sulfuric acid and oxalic acid.

[0015] As a preferred embodiment of the method for preparing the medical attapulgite particles with a spherical porous structure described in the present invention, in step S1, the mass fraction of the attapulgite powder is 20-30%;

[0016] In step S2, the mass fractions of anhydrous ethanol, pore-forming agent and surfactant are 30-50%, 5-15% and 10-15% respectively;

[0017] In step S1, the mass fraction of the attapulgite powder is 20-30%, wherein the surfactant accounts for 50% of the mass of the attapulgite powder.

[0018] As a preferred embodiment of the method for preparing the medical attapulgite particles with a spherical porous structure described in the present invention, in step S2, the surfactant is octadecyltrimethylammonium bromide or dioctadecyldimethylammonium bromide, and the pore-forming agent is PVA.

[0019] As a preferred embodiment of the method for preparing medical attapulgite particles with a spherical porous structure described in the present invention, in step S3, the parameters for preparing attapulgite microspheres by electrospraying are: voltage 20-30 kV, electrospraying distance 30-40 cm, and electrospraying precursor solution boosting speed 2-5 ml / h.

[0020] As a preferred embodiment of the method for preparing the medical attapulgite particles with a spherical porous structure according to the present invention, in step S4, the high-temperature sintering step is as follows:

[0021] First, heat up to 200°C at 10°C / min and keep warm for 1-2 hours. Then, heat up to 400-500°C at 2-4°C / min and keep warm for 1-4 hours.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. The present invention is the first to use the electrostatic spraying method for the preparation of attapulgite microspheres. The obtained microsphere particles have a very high sphericity, which retains the original large specific surface area of ​​the attapulgite and at the same time increases the porosity of the particles, giving full play to the strong adsorption capacity of the attapulgite.

[0024] 2. The attapulgite microspheres prepared by the present invention can overcome the shortcomings of poor fluidity and poor dispersion effect of traditional attapulgite materials, and at the same time can achieve adjustable porosity inside the microspheres. For applications in the field of biomedicine, the attapulgite microspheres can be better mixed with organic solvents to improve the application effect of attapulgite. At the same time, the porous microsphere attapulgite particles can also further improve their use effect as thermal insulation materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the present invention will be described in detail below in combination with the accompanying drawings and detailed embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0026] Figure 1 is a structural diagram of the attapulgite powder used in the embodiments of the present invention;

[0027] Figure 2 This is a structural diagram of the attapulgite microspheres in Example 1 of the present invention. DETAILED DESCRIPTION

[0028] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0029] Secondly, the present invention is described in detail with reference to schematic diagrams. When describing the embodiments of the present invention in detail, for the sake of convenience, the cross-sectional diagrams showing the device structure will not be partially enlarged according to the general scale, and the schematic diagrams are only examples, which should not limit the scope of protection of the present invention. In addition, in actual production, the three-dimensional dimensions of length, width and depth should be included.

[0030] In order to make the objectives, technical solutions and advantages of the present invention more clear, the embodiments of the present invention will be further described in detail below with reference to the accompanying drawings.

[0031] The present invention provides a method for preparing medical attapulgite particles with a spherical porous structure, which effectively solves the problems of poor fluidity and low dispersibility of the attapulgite particles and improves the application effect of the attapulgite particles in the field of biomedicine.

[0032] Example 1

[0033] S1. Weigh attapulgite powder according to the mass ratio of 1:2:2:5. Figure 1 As shown, anhydrous ethanol, dilute hydrochloric acid solution and zirconium oxide grinding balls are put into a ball mill for 6 hours at a speed of 1000 r / min, washed with deionized water, dried and sieved;

[0034] S2, prepare the precursor electrospray liquid according to the mass ratio, wherein the mass fractions of anhydrous ethanol, PVA, octadecyltrimethylammonium bromide and attapulgite powder in S1 are 40%, 15%, 15% and 30% respectively, disperse them by ultrasonic in a 50°C water bath, mix them evenly and load them into the injector;

[0035] S3, attapulgite microspheres were prepared by electrostatic spraying, the parameters were: voltage 20 kV, electrospraying distance 30 cm, electrospraying precursor solution boosting speed 4 ml / h;

[0036] S4, the attapulgite microspheres obtained in step S3 were washed with deionized water and dried at 100°C for 2 hours. Then the temperature was raised to 200°C at 10°C / min and kept at this temperature for 2 hours; then the temperature was raised to 500°C at 2°C / min and kept at this temperature for 4 hours. After sintering, the following was obtained: Figure 2 The porous spherical attapulgite particles shown.

[0037] Example 2

[0038] S1. Weigh attapulgite powder, anhydrous ethanol, dilute hydrochloric acid solution and zirconium oxide grinding balls in a mass ratio of 1:2:2:5, put them into a ball mill and mill them for 6 hours at a speed of 1000r / min. Wash with deionized water, dry and sieve;

[0039] S2, preparing a precursor electrospray liquid according to a mass ratio, wherein the mass fractions of anhydrous ethanol, PVA, octadecyltrimethylammonium bromide and the attapulgite powder prepared in step S1 are 42.5%, 12.5%, 15% and 30% respectively, and ultrasonically dispersing them in a 50°C water bath, mixing them evenly and loading them into a push syringe;

[0040] S3, attapulgite microspheres were prepared by electrostatic spraying, the parameters were: voltage 20 kV, electrospraying distance 30 cm, electrospraying precursor solution boosting speed 4 ml / h;

[0041] S4, the attapulgite microspheres obtained in step S3 are washed with deionized water and dried at 100°C for 2 hours. Then the temperature is raised to 200°C at 10°C / min and kept at this temperature for 2 hours; then the temperature is raised to 500°C at 2°C / min and kept at this temperature for 4 hours. After sintering, porous spherical attapulgite particles are obtained.

[0042] Example 3

[0043] S1. Weigh attapulgite powder according to the mass ratio of 1:2:2:5. Figure 1 As shown, anhydrous ethanol, dilute hydrochloric acid solution and zirconium oxide grinding balls are put into a ball mill for 6 hours at a speed of 1000 r / min, washed with deionized water, dried and sieved;

[0044] S2, prepare the precursor electrospray liquid according to the mass ratio, wherein the mass fractions of anhydrous ethanol, PVA, octadecyltrimethylammonium bromide and the attapulgite powder in step 1 are 45%, 10%, 15% and 30% respectively, disperse them by ultrasonic in a 50°C water bath, mix them evenly and load them into the injector;

[0045] S3, attapulgite microspheres were prepared by electrostatic spraying, the parameters were: voltage 20 kV, electrospraying distance 30 cm, electrospraying precursor solution boosting speed 4 ml / h;

[0046] S4, the attapulgite microspheres obtained in step S3 were washed with deionized water and dried at 100°C for 2 hours. Then the temperature was raised to 200°C at 10°C / min and kept at this temperature for 2 hours; then the temperature was raised to 500°C at 2°C / min and kept at this temperature for 4 hours. After sintering, the following was obtained: Figure 2 The porous spherical attapulgite particles shown.

[0047] Example 4

[0048] S1. Weigh attapulgite powder according to the mass ratio of 1:2:2:5. Figure 1 As shown, anhydrous ethanol, dilute hydrochloric acid solution and zirconium oxide grinding balls are put into a ball mill for 6 hours at a speed of 1000 r / min, washed with deionized water, dried and sieved;

[0049] S2, prepare the precursor electrospray liquid according to the mass ratio, wherein the mass fractions of anhydrous ethanol, PVA, octadecyltrimethylammonium bromide and attapulgite powder in S1 are 40%, 15%, 15% and 30% respectively, disperse them by ultrasonic in a 50°C water bath, mix them evenly and load them into the injector;

[0050] S3, electrostatic spraying was used to prepare attapulgite microspheres. The parameters were: voltage 20 kV, electrospray distance 35 cm, electrospray precursor solution boosting speed 4 ml / h;

[0051] S4, the attapulgite microspheres obtained in step S3 were washed with deionized water and dried at 100°C for 2 hours. Then the temperature was raised to 200°C at 10°C / min and kept at this temperature for 2 hours; then the temperature was raised to 500°C at 2°C / min and kept at this temperature for 4 hours. After sintering, the following was obtained: Figure 2 The porous spherical attapulgite particles shown.

[0052] Example 5

[0053] S1. Weigh attapulgite powder according to the mass ratio of 1:2:2:5. Figure 1 As shown, anhydrous ethanol, dilute hydrochloric acid solution and zirconium oxide grinding balls are put into a ball mill for 6 hours at a speed of 1000 r / min, washed with deionized water, dried and sieved;

[0054] S2, prepare the precursor electrospray liquid according to the mass ratio, wherein the mass fractions of anhydrous ethanol, PVA, octadecyltrimethylammonium bromide and attapulgite powder in S1 are 40%, 15%, 15% and 30% respectively, disperse them by ultrasonic in a 50°C water bath, mix them evenly and load them into the injector;

[0055] S3, electrostatic spraying was used to prepare attapulgite microspheres. The parameters were: voltage 20 kV, electrospraying distance 40 cm, electrospraying precursor solution boosting speed 4 ml / h;

[0056] S4, the attapulgite microspheres obtained in step S3 were washed with deionized water and dried at 100°C for 2 hours. Then the temperature was raised to 200°C at 10°C / min and kept at this temperature for 2 hours; then the temperature was raised to 500°C at 2°C / min and kept at this temperature for 4 hours. After sintering, the following was obtained: Figure 2 The porous spherical attapulgite particles shown.

[0057] Example 6

[0058] S1. Weigh attapulgite powder according to the mass ratio of 1:2:2:5. Figure 1 As shown, anhydrous ethanol, dilute hydrochloric acid solution and zirconium oxide grinding balls are put into a ball mill for 6 hours at a speed of 1000 r / min, washed with deionized water, dried and sieved;

[0059] S2, prepare the precursor electrospray liquid according to the mass ratio, wherein the mass fractions of anhydrous ethanol, PVA, octadecyltrimethylammonium bromide and attapulgite powder in S1 are 40%, 15%, 15% and 30% respectively, disperse them by ultrasonic in a 50°C water bath, mix them evenly and load them into the injector;

[0060] S3, attapulgite microspheres were prepared by electrostatic spraying, the parameters were: voltage 25 kV, electrospraying distance 30 cm, electrospraying precursor solution boosting speed 4 ml / h;

[0061] S4, the attapulgite microspheres obtained in step S3 were washed with deionized water and dried at 100°C for 2 hours. Then the temperature was raised to 200°C at 10°C / min and kept at this temperature for 2 hours; then the temperature was raised to 500°C at 2°C / min and kept at this temperature for 4 hours. After sintering, the following was obtained: Figure 2 The porous spherical attapulgite particles shown.

[0062] Table 1 shows the test results of particle size, porosity and fluidity of the attapulgite microspheres in Examples 1 to 6. The powder fluidity test uses a Hall flowmeter (ASTM 213) to measure the time it takes for 50 g of powder to flow through. It can be seen from Table 1 that the microsphere particles obtained in Examples 1 to 6 have very high sphericity, porosity and fluidity, overcoming the shortcomings of poor fluidity and poor dispersion effect of traditional attapulgite materials.

[0063] Table 1

[0064]

[0065] Although the present invention has been described above with reference to the embodiments, various modifications may be made thereto and parts thereof may be replaced by equivalents without departing from the scope of the present invention. In particular, as long as there is no structural conflict, the various features in the embodiments disclosed in the present invention may be used in combination with each other in any manner, and the fact that these combinations are not exhaustively described in this specification is only for the sake of omitting space and saving resources. Therefore, the present invention is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.

Claims

1. A method for preparing medical attapulgite particles with a spherical porous structure, characterized in that: Here are the steps: S1, weighing attapulgite powder and putting it into a ball mill, adding zirconium oxide grinding balls, anhydrous ethanol and acid solution in proportion, and fully ball milling, washing with deionized water, drying and sieving to obtain attapulgite powder of uniform size; S2, mixing the obtained attapulgite powder with a surfactant, anhydrous ethanol, and a pore-forming agent in proportion, and uniformly dispersing the mixture by ultrasonication in a 50-70° C. water bath or oil bath to obtain an electrospray precursor solution; S3, loading the obtained electrospray precursor solution into a push injection device, the microsphere receiving device is filled with a mixed solution of dilute hydrochloric acid and anhydrous ethanol, applying voltage to the push injection device for electrospraying, and obtaining microspheres in the microsphere receiving device; S4. The obtained microspheres are washed with deionized water, dried at 100° C. for 2-3 hours, and then sintered at high temperature to obtain attapulgite microspheres with a spherical porous structure.

2. The method for preparing a spherical porous medical attapulgite particle according to claim 1, characterized in that: In step S1, the mass ratio of attapulgite powder, anhydrous ethanol, acid solution and zirconium oxide grinding balls is 1:2:2:

5.

3. The method for preparing a spherical porous medical attapulgite particle according to claim 1, characterized in that: In step S1, the zirconium oxide grinding balls include large balls with a diameter of 1 mm and small balls with a diameter of 0.2 mm, the mass ratio of the large balls to the small balls is 1:4, the ball milling time is 6-8 hours, and the rotation speed is 1000-2000 r / min.

4. The method for preparing a spherical porous medical attapulgite particle according to claim 1, characterized in that: In step S1, the acid solution is any one of dilute hydrochloric acid, dilute sulfuric acid and oxalic acid.

5. The method for preparing the medical attapulgite particles with a spherical porous structure according to claim 1, characterized in that: In step S1, the mass fraction of attapulgite powder is 20-30%; In step S2, the mass fractions of anhydrous ethanol, pore-forming agent and surfactant are 30-50%, 5-15% and 10-15% respectively; In step S1, the mass fraction of the attapulgite powder is 20-30%, wherein the surfactant accounts for 50% of the mass of the attapulgite powder.

6. The method for preparing the medical attapulgite particles with a spherical porous structure according to claim 1, characterized in that: In step S2, the surfactant is octadecyltrimethylammonium bromide or dioctadecyldimethylammonium bromide, and the pore-forming agent is PVA.

7. The method for preparing the medical attapulgite particles with a spherical porous structure according to claim 1, characterized in that: In step S3, the parameters for preparing attapulgite microspheres by electrospraying are: voltage 20-30 kV, electrospraying distance 30-40 cm, and electrospraying precursor solution boosting speed 2-5 ml / h.

8. The method for preparing medical attapulgite particles with a spherical porous structure according to claim 1, characterized in that: In step S4, the high temperature sintering step is as follows: First, heat up to 200°C at 10°C / min and keep warm for 1-2 hours. Then, heat up to 400-500°C at 2-4°C / min and keep warm for 1-4 hours.